The myeloid 7/4-antigen defines recently generated inflammatory macrophages and is synonymous with Ly-6B. - Rosas, M; Thomas, B; Stacey, M; Gordon, S; Taylor, P (2010)
This study aimed to identify the inflammation-associated 7/4-antigen, which is highly expressed on neutrophils, inflammatory monocytes, some activated macrophages, as well as on bone marrow myeloid-restricted progenitors. The high expression on inflammatory cells is suggestive of a role in inflammation and makes the 7/4-antigen a potential target for the manipulation of inflammatory cells. Consistent with this, the 7/4-antibody mediates specific depletion of 7/4-expressing neutrophils and monocytes. We have identified the 7/4-antigen as a 25- to 30-kDa GPI-anchored glycoprotein synonymous with the Ly-6B.2 alloantigen. We characterized the expression of Ly-6B during the inflammatory reaction induced by zymosan. During the later stages of an experimental, acute, self-resolving inflammatory response, we found that Ly-6B is differentially expressed on macrophages. Ly-6B-expressing macrophages also express more MHCII, CIITA, CCR2, Ly-6C, and CD62L than the Ly-6B-negative macrophages, which in turn, express more of the resident tissue macrophage marker SIGN-R1 and higher CD11b and F4/80. Ly-6B-expressing macrophages incorporate more BrdU than their Ly-6B-negative contemporaries when fed during the resolution phase of the acute inflammatory response. Thus, Ly-6B expression on mature macrophages defines a subset of recently generated inflammatory macrophages that retain monocytic markers and is hence a surrogate marker of macrophage turnover in inflammatory lesions. The definition of the 7/4:Ly-6B antigen will allow further characterization and specific modulation of Ly-6B-expressing cells in vivo.